SELECTION OF REFERENCE VALUE OF LONGITUDINAL TO TRANSVERSAL ULTRASONIC WAVES VELOCITY RATIO ON PRESSURE PURPOSE STEELS FOR DETECTION OF CREEP - Tomáš Zavadil (Acta Polytechnica CTU Proceedings, 2018)
Common degradation process for industrial equipment in power and petrochemical industry is creep. The ultrasonic waves velocities and their ratio can provide feedback on stress-strain conditions generated by heat. Selection of potentially critically affected parts of pressure equipment can be theoretically accessed by their means. Selection of such critical parts or areas is done by comparison with reference benchmark value. Setting the standard reference value for conventional pressure purpose steel is crucial so it can be later used as a benchmark for selection of critical areas on equipment under operation. The article proposes a benchmark value to be utilized for P265GH pressure purpose steel and steels of similar grade.